A comparison of immersive virtual reality with traditional neuropsychological measures in the assessment of executive functions. Issue 2 (9th May 2017) - Davison, Sophie Melissa Clare; Deeprose, Catherine; Terbeck, Sylvia
Abstract : Objective: This study investigated immersive virtual reality (IVR), as a novel technique to test executive function of healthy younger and older adults. We predicted IVR tasks to have greater predictive power than traditional measures when assessing age-related cognitive functioning due to the real-world validity of the tasks. Methods: Participants ( n =40) completed the Stroop colour–word test and the trail-making test (TMT) as traditional and commonly used assessments of executive functioning. Participants then completed three IVR tasks; a seating arrangement task, an item location task (both set in a virtual chemistry lab), and a virtual parking simulator. Results: Younger adults completed significantly more parking simulator levels ( p <0.001), placed significantly more objects ( p <0.001), and located significantly more items than older adults ( p <0.01), demonstrating higher levels of performance. Significant correlations were found between performance on traditional neuropsychological measures and IVR measures. For example, Stroop CW performance significantly correlated with the number of parking simulator levels completed (τ=0.43, p <0.01). This suggests that IVR measures assess the same underlying cognitive constructs as traditional tasks. In addition, IVR measures contributed a significant percentage of the explained variance in age. Conclusion: IVR measures (i.e. number of parking simulator levels completed and number of objects placed in the seating arrangement task) were found to be stronger contributors than existing traditional neuropsychological tasks in predicting age-related cognitive decline. Future research should investigate the implementation of these real-world-based tasks in clinical groups given this promising initial work.